Helping an elderly patient live with CHF - Efat Sahba (Iran University of Medical Sciences, 1993)
When I first met this nice lady, I was in an evening work shift of CCU. This 69 years-old woman had been referred recently to our ward. She had a pale and puffy face. She suffered from CHF. She had a normal breathing, but her ankle was swollen.   We stabilized her condition easily but, it was just the first step in her treatment way. Prevention of recurrence of heart attack was our goal. Every year, Congestive Heart Failure causes numerous patients' hospitalization in order to prevention and treatment of heart attacks.